Applying the P5 standard for sustainability: Enriching project leadership - Van Rooyen, E. J. (International Conference on Public Administration and Development Alternatives (IPADA), 2019)
Modern-day project management seeks to balance the time-cost-scope triple constraint forces associated with project execution, whilst accommodating risk and optimising the value and benefits, that the milieu brings to a project's doorstep. It is here where the P5 Standard may become a handy tool for a project leader to pursue sustainability. The P5 Standard focuses on the impact of processes and impacts that projects may have on the natural environment, society, the corporate bottom line and local economy; all in the interest of people, planet, prosperity, process and products. This Standard seeks to align to the 2030 Agenda for Sustainable Development by integrating all aspects relating to a project with the 17 sustainable development goals (SDGs). In this paper, the P5 Impact Analysis is described and examples from a practitioner's point of view are cited for clarification. The point is made that the P5 may be a handy tool with which to enrich project leadership. It should be considered that currently, the P5 is the product of much empirical endeavour and as such academic and strong theory is limited. This article therefore delves into sources that emanate from practice and it is hoped that the P5 may find its way into the scholarly discourse. The narrative also forms part of an extended research endeavour along the shorelines of project management sustainability leadership
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Environmental bottom line; Leadership; Risk management; P5 Standard; Sustainability; Project management; Financial risk management